2018
DOI: 10.1371/journal.pone.0201209
|View full text |Cite
|
Sign up to set email alerts
|

How much does direct transmission between pigs contribute to Japanese Encephalitis virus circulation? A modelling approach in Cambodia

Abstract: Japanese Encephalitis (JE) is the most important cause of human encephalitis throughout Asia and the Pacific. Although JE is a vector-borne disease, it has been demonstrated experimentally that transmission between pigs can occur through direct contact. Whether pig-to-pig transmission plays a role in the natural epidemiological cycle of JE remains unknown. To assess whether direct transmission between pigs may occur under field conditions, we built two mathematical models of JE transmission incorporating vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…According to the sensitivity analysis results, model parameters had the same influence on model outputs in both breeding systems. In Diallo et al, the most influential parameter driving variations of the basic reproduction number (R 0 ) of two JE transmission models –one with vector borne transmission only and one incorporating both vector-borne and direct transmission, was the mosquito population size (61). Results of the sensitivity analyses in the present work are consistent with that: for both farming systems, the vector population size was the parameter that mostly influenced the maximal number of sows allowing epidemic die-out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the sensitivity analysis results, model parameters had the same influence on model outputs in both breeding systems. In Diallo et al, the most influential parameter driving variations of the basic reproduction number (R 0 ) of two JE transmission models –one with vector borne transmission only and one incorporating both vector-borne and direct transmission, was the mosquito population size (61). Results of the sensitivity analyses in the present work are consistent with that: for both farming systems, the vector population size was the parameter that mostly influenced the maximal number of sows allowing epidemic die-out.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological system was modeled by a host population (a pig herd) combined with a Culex mosquito vector population (mosquitoes). The dynamic of the epidemiological systems resulted from two distinct processes: the infectious process, operating in continuous time was adapted from (61), whereas the pig breeding process was modeled based on discrete events occurring instantaneously. A graphical representation of pig breeding processes and associated infectious dynamics is provided in Fig 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several in vivo experiments demonstrated that JEV can be excreted oronasally in infected pigs, independently of the route of inoculation, for a period of 5 days, with a maximum level of virus shedding reached after the end of viremia ( 8 12 ). Furthermore, mathematical modeling using data from outbreaks in Cambodian pig farms supported the possibility that direct transmission also occurs under field conditions ( 13 ). These findings represent a warning that JEV could have the potential to continue to circulate in the pig population by direct transmission in temperate regions during cold mosquito-free periods.…”
Section: Introductionmentioning
confidence: 99%